Ba\(_{1-x}\)Ca\(_{x}\)TiO\(_{3}\) and the Dielectric Properties - Khien, Nguyen Van; Lam, Vu Dinh; Hong, Le Van (Communications in Physics, 2014)
Ba1-xCaxTiO3 material samples with x changing from zero to 1 were fabricated by the solid state reaction method at a temperature of 1200 oC in the ambient atmosphere. Crystalline structure of the material samples was recorded and identified by X-ray diffraction and Raman scattering. Analyzing the X-ray patterns found that Ba can be completely substituted by Ca with the concentration lower than 11 at%. The frequency dependence of the impedance (C) and AC conductance (G) of all the samples were recorded in a frequency range lower than 10 MHz by using an impedance analyzer HP 4192A. It was found that in the low frequency range lower than 1 MHz the dielectric constant and its loss decrease as Ca substituted for Ba. Besides an abnormal in the frequency dependence of the dielectric constant was observed for all samples in the higher frequency range up to 10 MHz.